Balloon atrial septostomy through internal jugular vein in a 45-day-old child with transposition of great arteries - Padhi Sumanta; Bakshi Kinjal; Londhe Avinash (Wolters Kluwer Medknow Publications, 2010)
Balloon atrial septostomy is a common palliative procedure in D-transposition of great arteries. It is technically easy before 2-3 weeks of age when the septum primum is thin. Femoral vein or umbilical vein, when available, is the common access used for this procedure. In situations when these accesses are not available or in case of inferior vena cava interruption, trans-hepatic access is used. Internal jugular vein (IJV) access is not used as it is difficult to enter the left atrium through this route. We describe a case of successful Balloon atrial septostomy done through IJV in a 45-day-old child with emphasis on the technique, hardware and precautions necessary during the procedure.